Disney's Aladdin pop-up book - Haber, Jon Z.; Wakeman, Diana; Smith, Rodger; Walt Disney Company; Intervisual Communications, Inc. (New York : Disney Press, 1993)
With the aid of a genie from a magic lamp, Aladdin fights an evil magician and wins the hand of a beautiful princess.
Cover title.
"Produced by Intervisual Communications, Inc., Santa Monica, California"--P. [4] of cover.
"IBI: 471-07"--P. [4] of cover.
Keywords: Toy and movable books -- Specimens; Fairy tales; Arabs -- Folklore; Toy and movable books